An atomistic simulation study of nanoscale sintering: The role of grain boundary misorientation - Sestito, Jesse M.; Abdeljawad, Fadi; Harris, Tequila A.L.; Wang, Yan; Roach, Allen (Computational materials science, 2019)
[Display omitted] •Atomistic simulations were employed to investigate nanoscale sintering.•Particle neck growth was examined as a function of GB misorientation.•Pore shrinkage kinetics is highly dependent on the GBs present in the system. Sintering is a processing technique used to produce bulk materials from powder compacts. Recently, sintering has been the subject of active research for its relevance to a wide range of applications, such as additive manufacturing and fabrication of bulk nanocrystalline materials. Of particular interest is the role of grain boundaries (GBs) on sintering mechanisms, cooperative mass transport, and pore shrinkage rates. Herein, atomistic simulations are leveraged to investigate sintering kinetics and densification rates of nanoscale particles as a function of GB misorientation. The two-particle geometry is used to examine particle neck growth rates and crystallographic re-orientation events, and report relative GB diffusion rates as a function of GB misorientation. For the three-particle configuration, simulation results reveal a plethora of pore shrinkage profiles ranging from complete shrinkage to stagnant response depending on the GBs present in the system. This is the first atomistic study that systematically examines the role of GB misorientation on pore shrinkage rates. Our results highlight the need to revisit continuum sintering treatments in order to account for the anisotropy in GB properties.